ResA3: a web tool for resampling analysis of arbitrary annotations. - Aaron Ruhs (Public Library of Science (PLoS), 2013)
Resampling algorithms provide an empirical, non-parametric approach to determine the statistical significance of annotations in different experimental settings. ResA(3) (Resampling Analysis of Arbitrary Annotations, short: ResA) is a novel tool to facilitate the analysis of enrichment and regulation of annotations deposited in various online resources such as KEGG, Gene Ontology and Pfam or any kind of classification. Results are presented in readily accessible navigable table views together with relevant information for statistical inference. The tool is able to analyze multiple types of annotations in a single run and includes a Gene Ontology annotation feature. We successfully tested ResA using a dataset obtained by measuring incorporation rates of stable isotopes into proteins in intact animals. ResA complements existing tools and will help to evaluate the increasing number of large-scale transcriptomics and proteomics datasets (resa.mpi-bn.mpg.de).